Fatores que interferem no desempenho da deglutição de pacientes com traumatismo cranioencefálico - Saurim, Juliana Boza [UNIFESP] (2017)
Traumatic Brain Injury (TBI) is one of the leading causes of disability and mortality. Dysphagia can be highlighted as a sequel due to neurological impairment, which is an alteration of the swallowing process and can rehabilitated by a speech therapist, along with a multi professional staff. Aim: Analyze factors that interferes in the swallowing performance of TBI's patients admitted in the intensive care unit (ICU). Method: Medical records from August 2007 to May 2016 of TBI's patients, who underwent speech pathologist clinical evaluation at the bedside in the ICU of São Paulo Hospital – H.U. São Paulo Federal University were analyzed. The patients were divided into two groups: G1 = were discharged from the hospital or died due to at least one oral food consistency feeding and G2 = were discharged from the hospital or died due to feeding exclusively by an alternate via. The cases were identified through demographic, clinical and radiological data. The initial and final swallowing performance was measured using the Functional Oral Intake Scale (FOIS), Dysphagia Outcome Severity Scale (DOSS) and ASHA-NOMS Scale. Results: 62% of the patients presented oral feeding reintroduction. The G2 group was significantly older, IOT days, tracheostomy individuals, cognitive status altered, severe dysphagia diagnosis, severe traumas according to ECG and secondary lesions associated. The swallowing functional performance of G1 group evolved from level 2 to level 5 on the applied scales and oral feeding reintroduction started in the second therapy session. Conclusions: Age, IOT time, TQT, cognitive status altered, trauma severity and secondary lesions influenced negatively in swallowing. It was possible to reintroduce oral feeding in the majority of the patients and these progressed significantly in the performance.